Ответ:
[tex]132)16 \frac{1}{3} - 11 \frac{3}{7} \times ( \frac{1}{10} + \frac{2}{15} ) = 16 \frac{1}{3} - \frac{80}{7} \times \frac{3 + 4}{30} = 16 \frac{1}{3} - \frac{80 \times 7}{7 \times 30} = 16 \frac{1}{3} - \frac{8}{3} = 15 \frac{4}{3} - 2 \frac{2}{3} = 13 \frac{2}{3} [/tex]
[tex]133)(2 \frac{1}{3} - 2 \frac{5}{6} ) \div 1 \frac{1}{6} + 5 \frac{3}{14} = (2 \frac{2}{6} - 2 \frac{5}{6} ) \div \frac{7}{6} + 5 \frac{3}{14} = - \frac{3}{6} \div \frac{7}{6} + 5 \frac{3}{14} = - \frac{3 \times 6}{6 \times 7} + 5 \frac{3}{14} = - \frac{3}{7} + 5 \frac{3}{14} = - \frac{6}{14} + 4 \frac{17}{14} = 4 \frac{11}{14} [/tex]
[tex]134)(3 \frac{3}{4} \times 2 - 9) \div ( - \frac{7}{8} ) = ( \frac{15 \times 2}{4} - 9) \div ( - \frac{7}{8} ) = ( \frac{15}{2} - 9) \div ( - \frac{7}{8} ) = (7.5 - 9) \div ( - \frac{7}{8} ) = - 1.5 \div ( - \frac{7}{8} )= \frac{3}{2} \div \frac{7}{8} = \frac{3 \times 8}{2 \times 7} = \frac{12}{7} [/tex]
[tex]135)( \frac{5}{48} \times 3 \frac{1}{5} - \frac{1}{2} ) \div ( - \frac{2}{45} ) - 2 = ( \frac{5}{48} \times \frac{16}{5} - \frac{1}{2} ) \div ( - \frac{2}{45} ) - 2 = ( \frac{1}{3} \times \frac{1}{2} ) \div ( - \frac{2}{45} ) - 2 = \frac{5}{6} \div ( - \frac{2}{45} ) - 2 = - \frac{5 \times 45}{6 \times 2} - 2= - \frac{75}{4} - 2 = - 18.75 - 2 = - 20.75[/tex]
[tex]136)(5 \frac{3}{8} + 18 \frac{1}{2} - 7 \frac{5}{24} ) \div 16 \frac{2}{3} = (5 \frac{9}{24} + 18 \frac{12}{24} - 7 \frac{5}{24} ) \div 16 \frac{2}{3} = 16 \frac{16}{24} \div 16 \frac{2}{3} = 16 \frac{2}{3} \div 16 \frac{2}{3} = 1[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]132)16 \frac{1}{3} - 11 \frac{3}{7} \times ( \frac{1}{10} + \frac{2}{15} ) = 16 \frac{1}{3} - \frac{80}{7} \times \frac{3 + 4}{30} = 16 \frac{1}{3} - \frac{80 \times 7}{7 \times 30} = 16 \frac{1}{3} - \frac{8}{3} = 15 \frac{4}{3} - 2 \frac{2}{3} = 13 \frac{2}{3} [/tex]
[tex]133)(2 \frac{1}{3} - 2 \frac{5}{6} ) \div 1 \frac{1}{6} + 5 \frac{3}{14} = (2 \frac{2}{6} - 2 \frac{5}{6} ) \div \frac{7}{6} + 5 \frac{3}{14} = - \frac{3}{6} \div \frac{7}{6} + 5 \frac{3}{14} = - \frac{3 \times 6}{6 \times 7} + 5 \frac{3}{14} = - \frac{3}{7} + 5 \frac{3}{14} = - \frac{6}{14} + 4 \frac{17}{14} = 4 \frac{11}{14} [/tex]
[tex]134)(3 \frac{3}{4} \times 2 - 9) \div ( - \frac{7}{8} ) = ( \frac{15 \times 2}{4} - 9) \div ( - \frac{7}{8} ) = ( \frac{15}{2} - 9) \div ( - \frac{7}{8} ) = (7.5 - 9) \div ( - \frac{7}{8} ) = - 1.5 \div ( - \frac{7}{8} )= \frac{3}{2} \div \frac{7}{8} = \frac{3 \times 8}{2 \times 7} = \frac{12}{7} [/tex]
[tex]135)( \frac{5}{48} \times 3 \frac{1}{5} - \frac{1}{2} ) \div ( - \frac{2}{45} ) - 2 = ( \frac{5}{48} \times \frac{16}{5} - \frac{1}{2} ) \div ( - \frac{2}{45} ) - 2 = ( \frac{1}{3} \times \frac{1}{2} ) \div ( - \frac{2}{45} ) - 2 = \frac{5}{6} \div ( - \frac{2}{45} ) - 2 = - \frac{5 \times 45}{6 \times 2} - 2= - \frac{75}{4} - 2 = - 18.75 - 2 = - 20.75[/tex]
[tex]136)(5 \frac{3}{8} + 18 \frac{1}{2} - 7 \frac{5}{24} ) \div 16 \frac{2}{3} = (5 \frac{9}{24} + 18 \frac{12}{24} - 7 \frac{5}{24} ) \div 16 \frac{2}{3} = 16 \frac{16}{24} \div 16 \frac{2}{3} = 16 \frac{2}{3} \div 16 \frac{2}{3} = 1[/tex]